(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article addresses the issues of effectively organizing independent learning activities of students in the academic lyceums under the Ministry of Internal Affairs. In particular, it presents proposals and recommendations for organizing independent learning activities through a web-based platform.